Mahdī Masīḥ kī ṣadī : bainulaqvāmī peshgoʼiyoṉ kā majmūʻah - Gẖāzī Munajjam (Gẖāzī Munajjim, 1980)
Predictions by a Pakistani astrologer about the world affairs, with particular reference to the appearance of the promised Messiah in the Panjab, Pakistan, the early 1980's.